Investigación de diversos factores que influyen en la salud mental percibida en la participación en actividades físicas en Sumatra Occidental, Indonesia: un enfoque que utiliza SEM-PLS (Investigating various factors that influence perceived mental health in physical activity participation in West Sumatera, Indonesia: An approach using SEM-PLS): Factors that affect the Mental Health of sports Participants - Sepdanius, Endang; Bin Mohd Sidi, M. Adli; Binti Sanuddin, Nurul Diyana; Afriani , Rini; Orhan, Bekir; Mario , Deby (Retos, 2024)
Problem Statement. Individual involvement in physical activity or sports is significant for the survival of a healthy and quality life, so the supporting and influencing factors need to be investigated. Purpose. This study aims to test a model related to factors that influence perceptions of mental health, including cognitive awareness, emotions, spirituality, and social environment for sports participants. Methods. A total of 1,351 volunteers from 18 regions in West Sumatra participated in this study. The data collection technique used a survey via Google Forms, distributed via WhatsApp social media. Data were analyzed using the Partial Least Square (PLS) method by assessing content validity, Average Variance Extracted (AVE), Inner Model, and hypothesis testing. Result. The results showed that cognitive awareness significantly affects awareness of the social environment (t = 13.142; P<0.05) and perceptions of mental health (t = 4.458; P<0.05). Emotional awareness significantly affects the relationship between awareness of the social environment (t = 5.572; P<0.05) and perceptions of mental health (t = 4.870; P<0.05). Environmental and social awareness significantly affects mental health perceptions (t = 7.397; P<0.05). Spiritual awareness significantly affects awareness of the social environment (t = 4.014; P<0.05) and perceptions of mental health (t = 5.851; P<0.05). Conclusions. Cognitive, emotional, and spiritual awareness and social environment are essential in influencing perceptions of mental health in individuals participating in sports. The findings highlight the importance of paying attention to cognitive, emotional, spiritual, and social environmental aspects of mindfulness for the sports community or other stakeholders to help create an environment that supports the quality of life of participants involved in sports. Key Words: Mental health, Cognitive, Emotional, Spiritual, Environment, Sports participants.